Increased brain activation and functional connectivity after working memory training in patients with ischemic stroke: an fMRI study - Chen, Zhengwei; Yun, Xiaoping (Frontiers in Stroke, 2023)
Objective: Working memory (WM) impairment is common in post-stroke patients. WM training (WMT) has been suggested to improve cognitive function. However, the neural effects following WMT in stroke patients remains largely unclear. This study aimed to explore behavior and neural effects of WMT on patients with chronic ischemic stroke.Methods: Fifty first-ever ischemic stroke patients with WM deficits during chronic stage were randomly assigned to either a 4-week WMT group or a control group. Verbal n-back, digital and spatial memory-span, Raven's standard progressive matrices and Stroop color-word test, as well as task-state and resting-state fMRI were assessed for all patients at baseline and after the intervention.WMT group showed improvements on WM, fluid intelligence and attention after training. Additionally, WMT group exhibited increased activation in left middle frontal gyrus (MFG) and middle occipital gyrus after training. At baseline, all patients were impaired in their abilities to elevate activation in WM network as a response to increasing WM load. However, in WMT group, increased activation was observed in left cerebellum anterior lobe, right cerebellum posterior lobe (CPL) and MFG in the 2-back vs. 1-back contrast after WMT. We also found increased functional connectivity between left MFG and left inferior parietal lobule (IPL), and between bilateral IPL and right CPL after training in WMT group. Conclusions: Our study supported that WMT potentially improved WM capacity in ischemic stroke patients during chronic stage, and the training effects might transfer to fluid intelligence and attention ability. Our results also demonstrated that repeated WMT potentially increased brain activation and resting-state functional connectivity within WM network in patients with ischemic stroke. These findings provided robust evidence supporting WMT as an effective intervention to enhance cognitive rehabilitation, and shed light on the functional neuroplasticity mechanism of WMT on cognitive recovery after ischemic stroke.